Glass material and optical fiber

By adjusting the single bond and double bond concentration ratio of Group 15 elements in glass and combining with silica-based glass, the problem of poor transmissibility of glass materials in wide wavelength regions under high temperature processing is solved, and high transmissibility and low loss are achieved. Glass material and optical fiber.

CN119403767APending Publication Date: 2025-02-07SUMITOMO ELECTRIC INDUSTRIES LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380048151.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-29
Filing Date
2023-06-06
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In glass containing Group 15 elements, high temperature processing leads to an increase in viscosity and glass transition temperature, easily introduce impurities, resulting in absorption problems, and it is difficult to achieve high transmittance in wide wavelength regions.

Method used

By adjusting the single bond and double bond concentration ratio of Group 15 elements (such as nitrogen, phosphorus, arsenic, and antimony), it satisfies [single bond]/[double bond] ≥1, combined with silica-based glass, it is prepared in The wide wavelength region has high transmittance glass materials and optical fibers.

Benefits of technology

High transmittance in wide wavelength regions is achieved, transmission loss is reduced, and absorption problems caused by the introduction of impurities are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005196119630000011
    Figure HDA0005196119630000011
  • Figure HDA0005196119630000012
    Figure HDA0005196119630000012
Patent Text Reader

Abstract

The glass material contains silica-based glass and a Group 15 element, and the concentration ratio of the single bond to the multiple bond of the Group 15 element satisfies [single bond] / [multiple bond] > = 1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a glass material and an optical fiber. This application claims priority based on Japanese Application No. 2022-104468 filed on June 29, 2022, and all the contents described in the Japanese Application are incorporated herein by reference. Background Art

[0002] Non-patent document 1 discloses that the refractive index increases in oxynitride glass, i.e., nitrogen-containing glass. Non-patent document 2 discloses that ultraviolet absorption shifts toward the short wavelength side in phosphorus-containing glass. Glass containing Group 15 elements represented by nitrogen and phosphorus can generally shift ultraviolet absorption toward the short wavelength side compared to pure silica glass, and can therefore be used as optical glass in a wide wavelength range.

[0003] Prior art literature

[0004] Non-patent literature

[0005] Non-patent document 1: Hampshire, Pomeroy, "Oxynitride Glasses", Int. J. Appl. Ceram. Technol., 5[2]155-163 (2008)

[0006] Non-patent document 2: Hirohei Kadono, "Optical properties of glass I.", NEW GLASS Vol. 24 No. 1 p. 59-63 (2009) Summary of the invention

[0007] A glass material according to one embodiment of the present disclosure is a glass material composed of silica-based glass and containing a Group 15 element, wherein a concentration ratio of single bonds to double bonds of the Group 15 element satisfies [single bond] / [double bond]≥1. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 It is a cross-sectional view showing an optical fiber according to an embodiment.

[0009] Figure 2 It is a graph showing the relationship between the concentration ratio and the transmission loss. DETAILED DESCRIPTION

[0010] [Technical Problems to be Solved by the Present Disclosure]

[0011] Glass containing Group 15 elements, especially nitrogen, needs to be processed at high temperatures due to the increase in viscosity and glass transition temperature. As a result, processability deteriorates and impurities are easily mixed in, resulting in the possibility of absorption caused by impurities. In the art, glass materials and optical fibers having high transmittance in a wide wavelength range are desired.

[0012] An object of the present disclosure is to provide a glass material and an optical fiber having high transmittance in a wide wavelength range.

[0013] [Effects of the present disclosure]

[0014] According to the present disclosure, it is possible to provide a glass material and an optical fiber having high transmittance in a wide wavelength range.

[0015] [Description of Embodiments of the Present Disclosure]

[0016] First, the embodiments of the present disclosure are listed for explanation. (1) A glass material according to one embodiment of the present disclosure is a glass material comprising silica-based glass and a Group 15 element, wherein the concentration ratio of single bonds and double bonds of the Group 15 element satisfies [single bonds] / [double bonds] ≥ 1. In the glass material, high transmittance is achieved in a wide wavelength range.

[0017] (2) In the glass material of (1) above, the concentration ratio of single bonds and double bonds of the Group 15 element may satisfy [single bond] / [double bond] ≥ 9. In this case, higher transmittance is achieved in a wide wavelength region.

[0018] (3) In the glass material of (1) above, the concentration ratio of single bonds and double bonds of the Group 15 element may satisfy [single bond] / [double bond] ≥ 19. In this case, particularly high transmittance is achieved in a wide wavelength region.

[0019] (4) In the glass material of any one of (1) to (3), the relative refractive index difference based on the refractive index of silica glass may be -0.1% to 0.3%. When the glass material is used to form a core, excessive addition of down dopants to the cladding can be suppressed.

[0020] (5) The glass material according to any one of (1) to (4) above may contain 50% by mass or more of silica glass. In this case, adverse effects on optical properties are suppressed.

[0021] (6) The glass material according to any one of (1) to (5) above may further contain an alkali metal element, an alkaline earth metal element, a Group 13 element, or a halogen element. In this case, the valence state of the Group 15 element can be stabilized.

[0022] (7) A glass material according to another embodiment of the present disclosure is a glass material containing silica-based glass and a Group 15 element, wherein the concentration ratio of single bonds to multiple bonds of the Group 15 element satisfies [single bonds] / [multiple bonds] ≥ 1. In this glass material, high transmittance is achieved in a wide wavelength range.

[0023] (8) An optical fiber according to one embodiment of the present disclosure comprises: a core comprising silica-based glass and a Group 15 element; and a cladding comprising silica-based glass and surrounding the core, wherein the concentration ratio of single bonds and double bonds of the Group 15 element in the core satisfies [single bonds] / [double bonds] ≥ 1. In this optical fiber, since high transmittance is achieved in a wide wavelength region, loss in a transmission band is reduced.

[0024] [Details of the embodiments of the present disclosure]

[0025] Specific examples of the glass material and optical fiber disclosed in the present invention are described below with reference to the accompanying drawings. It should be noted that the present invention is not limited to these examples, but is represented by the claims, and is intended to include all changes within the meaning and scope equivalent to the claims. In the description of the drawings, the same elements are marked with the same reference numerals, and repeated descriptions are omitted.

[0026] (Glass material)

[0027] The glass material involved in this embodiment is, for example, an optical glass material. More specifically, the glass material is, for example, an optical fiber glass material, which is used to form the core of the optical fiber. The glass material is composed of a silica-based glass containing silica glass as a main component. The glass material also contains other elements other than silicon (Si) and oxygen (O) constituting the silica glass.

[0028] Glass materials may also contain elements that easily form cations, such as alkali metal elements, alkaline earth metal elements, Group 13 elements, and Group 14 elements. Examples of alkali metal elements include lithium (Li), sodium (Na), potassium (K), and rubidium (Rb). Examples of alkaline earth metal elements include magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba). Examples of Group 13 elements include boron (B), aluminum (Al), gallium (Ga), and indium (In). Examples of Group 14 elements include germanium (Ge), tin (Sn), and lead (Pb).

[0029] In particular, the glass material may contain an element that easily stabilizes the valence, such as an alkali metal element, an alkaline earth metal element, and an element of Group 13. As will be described below, these elements that easily stabilize the valence have an effect of stabilizing the valence of the Group 15 element added to the glass material.

[0030] The glass material may also contain a halogen element. Examples of the halogen element include fluorine (F), chlorine (Cl), bromine (Br), and iodine (I). Since the halogen element is an oxidant, it has the effect of stabilizing the valence of the Group 15 element added to the glass material as will be described below.

[0031] The glass material contains a Group 15 element. Examples of the Group 15 element include nitrogen (N), phosphorus (P), arsenic (As), antimony (Sb), and bismuth (Bi). The glass material may also contain a plurality of Group 15 elements. In the glass material, the concentration ratio of single bonds and double bonds of the Group 15 element satisfies [single bond] / [double bond]≥1. That is, the concentration (amount present) of the Group 15 element in a single bond state is greater than the concentration (amount present) of the Group 15 element in a double bond state. The concentration ratio of single bonds and double bonds of the Group 15 element may satisfy [single bond] / [double bond]≥9, or may satisfy [single bond] / [double bond]≥19.

[0032] In the glass material, the concentration ratio of the single bond and the multiple bond of the Group 15 element satisfies [single bond] / [multiple bond]≥1. That is, the concentration (existence amount) of the Group 15 element in a single bond state is greater than the concentration (existence amount) of the Group 15 element in a multiple bond state. The concentration ratio of the single bond and the multiple bond of the Group 15 element may satisfy [single bond] / [multiple bond]≥9, or may satisfy [single bond] / [multiple bond]≥19.

[0033] Nitrogen tends to take a trivalent state. In glass materials, nitrogen can take various bonding states, such as double bonds such as Si=N and single bonds such as Si-N. Generally, the stronger the bond strength, the better the chemical durability of the glass that can be produced. On the other hand, the stronger the bond strength, the more likely the viscosity and glass transition temperature will increase, so a higher temperature is required to process the glass. Processing at high temperatures easily causes impurities such as water to mix in, so it is not suitable for the production of optical glass.

[0034] By making the glass material contain more single bonds such as Si-N, the chemical durability can be improved compared to pure silica glass, and the viscosity and glass transition temperature can be maintained at a lower state. In order to increase the proportion of nitrogen in a single bond state, nitrogen can also be added under high temperature and high pressure as much as possible. Due to high temperature and high pressure, the triple bond of the nitrogen molecule (N2) is easily broken and nitrogen is added as a single bond. It is also possible to use plasma to ionize nitrogen, or use a substance containing more single bonds such as ammonia (NH3) as a raw material for addition.

[0035] It is known that arsenic and antimony have a tendency to take a valence of three, but in terms of the characteristics of the elements, they are more likely to take various valences than nitrogen and phosphorus. Therefore, the valence state of arsenic and antimony can also be stabilized by adding elements that are easy to stabilize the valence, such as alkali metal elements, alkaline earth metal elements, and halogen elements. In particular, halogen elements can also be added together. The molar concentration of the added arsenic and antimony as a whole can be more than 0.1 times and less than 10 times, or more than 2 times and less than 5 times, or more than 2.5 times and less than 3.5 times relative to the molar concentration of the added halogen elements as a whole.

[0036] Since phosphorus easily takes a valence of five, special attention needs to be paid. Compared with silicon, which has four bonds, phosphorus has five bonds. Therefore, if phosphorus replaces silicon, the extra one helps to form a double bond. As a result, the viscosity tends to increase. Furthermore, strain is imparted to the glass structure, which results in the generation of defects and increases the absorption component on the short wavelength side, i.e., in the ultraviolet region. Such glass materials are not suitable for optical glass that requires high transmittance in a wide wavelength region. Therefore, for phosphorus, a method of dispersing the number of bonds by adding elements such as alkali metal elements and alkaline earth metal elements can also be adopted.

[0037] If the total amount of alkali metal elements added (molar concentration) is x, and the total amount of alkaline earth metal elements added (molar concentration) is y, then x+2y can be 0.1 times or more and 10 times or more, 0.5 times or more and 2 times or less, or 0.9 times or more and 1.2 times or less relative to the amount of phosphorus added (molar concentration). Since alkali metal elements can bond with phosphorus at a ratio of 1:1 and make the bonding state of phosphorus a single bond, the amount of alkali metal elements added can also be greater than the amount of alkaline earth metal elements added.

[0038] The relative refractive index difference Δ of the glass material based on the refractive index of pure silica glass (SiO2), i.e., silica glass, can be greater than -0.1% and less than 0.3%, or greater than 0.0% and less than 0.3%, or greater than 0.1% and less than 0.3%. When such a glass material is used to form a core, it is possible to suppress excessive addition of downward dopants such as F to the cladding. Therefore, it is possible to suppress an increase in transmission loss caused by an increase in the doping concentration.

[0039] All Group 15 elements are upward dopants and are added according to the refractive index of the target glass material. Group 15 elements can also be added to the glass material as much as possible. If a single element is added, that is, only one Group 15 element is added, then in the case of phosphorus, the mass ratio can be more than 50 ppm, or more than 1000 ppm, or more than 50000 ppm. In the case of nitrogen, the mass ratio can be more than 50 ppm, or more than 1000 ppm, or more than 20000 ppm. In the case of arsenic, the mass ratio can be more than 50 ppm, or more than 1000 ppm, or more than 10000 ppm. In the case of antimony, the mass ratio can be more than 50 ppm, or more than 1000 ppm, or more than 6000 ppm. Here, the mass ratio refers to the mass fraction.

[0040] If phase separation of the additives occurs due to the addition of multiple elements, it will have an adverse effect on the optical properties. Therefore, the proportion of silica glass as the main component can be 50% or more, 80% or more, or 90% or more by mass ratio. Here, mass ratio refers to mass fraction.

[0041] The bonding state of phosphorus and oxygen is evaluated, for example, by X-ray photoelectron spectroscopy (XPS). The peak of the spectrum caused by the bonding state of P=O is confirmed to be between 533 and 535 eV. The peak of the spectrum caused by the bonding state of PO is confirmed to be between 532 and 533 eV. These peaks are fitted using a Gaussian function to determine the peaks. Based on the area intensity ratio of the obtained fitting function, the concentration ratio of the bonding state (the ratio of the amount of the bonding state) is calculated.

[0042] The bonding state of nitrogen and silicon is also evaluated by XPS, for example. In the case of a double bond (Si=N), a peak of the spectrum is observed at 397.9 eV. In the case of only a single bond (Si-N), a peak of the spectrum is observed at 399.4 eV. These peaks are fitted using a Gaussian function and the peaks are determined. Based on the area intensity ratio of the obtained fitting function, the concentration ratio of the bonding state (the ratio of the amount of bonding state present) is calculated. The concentration ratio of single bonds and double bonds of nitrogen [N single bonds] / [N double bonds] can be greater than 1, greater than 9, or greater than 19.

[0043] The bonding state of arsenic and oxygen, and the bonding state of antimony and oxygen are also evaluated by XPS, for example. In the case of arsenic, the peak of the spectrum caused by trivalence is confirmed to be between 44.5 and 45.5 eV, and the peak of the spectrum caused by pentavalence is confirmed to be between 45.5 and 46.5 eV. In the case of antimony, the peak of the spectrum caused by trivalence is confirmed to be between 529.5 and 530.5 eV, and the peak of the spectrum caused by pentavalence is confirmed to be between 530.5 and 531.5 eV. These peaks are fitted using a Gaussian function and the peaks are determined. According to the area intensity ratio of the obtained fitting function, the concentration ratio of the bonding state (the ratio of the amount of bonding state) is obtained for arsenic and antimony, respectively.

[0044] The glass material is synthesized by a plasma melting method or a high pressure synthesis method, etc. In order to prevent the mixing of impurities as much as possible, the material of the furnace and other parts used in the production may be made of the same element as the glass material, that is, quartz.

[0045] (optical fiber)

[0046] Figure 1: is a cross-sectional view showing an optical fiber according to an embodiment. The optical fiber 1 according to the embodiment comprises: a core 10 extending along a central axis 1a; and a cladding 20 covering the core 10. The optical fiber 1 is formed using a glass material according to the embodiment. More specifically, the core 10 is formed using a glass material according to the embodiment. The cladding 20 is composed of a silica-based glass containing silica glass as a main component.

[0047] Table 1 shows the relationship between the concentration ratio and the transmission loss.

[0048] [Table 1

[0049] [N single bond] / [N double bond] Transmission loss [dB / km] 0.02 0.19 0.1 0.183 1 0.165 5.6 0.162 10 0.158 53 0.156 100 0.153 223 0.151 986 0.149

[0050] Figure 2 is a graph showing the relationship between the concentration ratio and the transmission loss. Figure 2 As shown, it can be seen that there is a tendency for the transmission loss to decrease as the concentration ratio increases. In the case of [N single bond] / [N double bond] ≥ 1, it can be confirmed that the transmission loss is suppressed to 0.165 dB / km or less.

[0051] As mentioned above, although embodiment was described, this disclosure is not necessarily limited to the said embodiment and modification, Various changes are possible within the range which does not deviate from the summary.

[0052] Description of Reference Numerals

[0053] 1. Fiber Optic

[0054] 1a Central axis

[0055] 10 Core

[0056] 20 cladding.

Claims

1. A glass material, It is a glass material containing silica-based glass and Group 15 elements. The concentration ratio of single bonds to double bonds of the Group 15 element satisfies [single bond] / [double bond]≥1.

2. The glass material according to claim 1, The concentration ratio of single bonds to double bonds of the Group 15 element satisfies [single bonds] / [double bonds]≥9.

3. The glass material according to claim 1, The concentration ratio of single bonds to double bonds of the Group 15 element satisfies [single bonds] / [double bonds]≥19.

4. The glass material according to any one of claims 1 to 3, The relative refractive index difference based on the refractive index of silica glass is not less than -0.1% and not more than 0.3%.

5. The glass material according to any one of claims 1 to 4, Contains 50% by mass or more of silica glass.

6. The glass material according to any one of claims 1 to 5, Alkali metal elements, alkaline earth metal elements, Group 13 elements or halogen elements are also included.

7. A glass material, It is a glass material containing silica-based glass and Group 15 elements. The concentration ratio of single bonds and multiple bonds of the Group 15 element satisfies [single bonds] / [multiple bonds]≥1.

8. An optical fiber having: A core comprising silica-based glass and a Group 15 element; and a cladding, comprising silica-based glass, surrounding the core, In the core, a concentration ratio of single bonds and double bonds of the Group 15 element satisfies [single bonds] / [double bonds]≥1.

Citation Information

Patent Citations

  • Hot runner assembly

    JP2022104468A